Elasmoid scales of fishes as model in biomedical bone research - Juriaan R. Metz; Erik de Vrieze; Erik‐Jan Lock; Ines E. Schulten; Gert Flik (2012)
With growing incidence of bone disorders (such as osteoporosis), the demand for fast and reliable alternatives to existing screens based on mammalian bone is increasing. Cell culture-based models that currently are being used, have limited value in the study of cell-cell and cell-matrix interactions. The dermal bone of fish scales offers an unprecedented and attractive model to study bone physiology, both in vivo and in vitro. The elasmoid scale of teleost fishes is of particular interest as it could stand as a model for direct bone formation as found in mammals and it has many advantageous traits: scales carry both bone-forming and bone-degrading cell populations, attached on their natural substrate, such that interactions between cell populations remain intact. The scale contains a collagen type-I matrix impregnated with apatites. Scales come in the hundreds per fish, are easily harvested and can be exposed in vitro for direct study of bone regulatory compounds. Scales are transparent allowing real-time visualization of cellular activities on either side of the scale. Removed scales are replaced quickly and the regeneration process strongly resembles osteogenesis as seen in early bone development. These advantages warrant more fundamental research on scales as models in biomedical bone research. We here address the state-of-the-art on development, structure and physiology of fish scales.